Proceso atención de enfermería en paciente adulto mayor con tumor maligno del pene - Cruz Álvarez, Kemberlin De Las Mercedes (2024)
The present clinical case study is applied to an elderly patient with a surgical pathological history of partial penectomy 4 months ago who was admitted as an emergency due to presenting a clinical picture of fever 38.4 and pain in the hypogastrium area, urinary retention, purulent and foul-smelling discharge that came from the urinary catheter that reflects in the collection bag. Blood pressure 122/78mmHg, heart rate 88bpm, respiratory rate 16rpm, temperature 38.4 and oxygen saturation 99% were recorded. Peripheral line #18 cannulation procedure is performed and pharmacological treatment is administered, according to medical prescription. During the physical assessment, the doctor observed abscessed inguinal lymph nodes and bladder balloon, an attempt was made to dilate the partial amputation meatus and there were no results. An attempt is made to place a cystotomy tube, but it is impossible. Emergency haematological and chemical biometry and conventional radiography will be performed. After having carried out the corresponding physical assessment and functional patterns of Marjory Gordon. As well as having obtained the laboratory results and imaging examinations, the patient was admitted as an emergency for a conventional cystotomy surgical procedure due to his diagnosis of malignant tumor of the penis. The patient is hospitalized in the internal medicine area where he will be provided with optimal nursing care according to his diagnosis.